Experimental investigations on FRP retrofitted RC beam-column specimens - Balasubramanian, K.; Lakshmanan, N.; Jeyasehar, C. Antony; Krishnamoorthy, T.S.; Bharatkumar, B.H. (Journal of Structural Engineering, 2024)
In the last few decades, moderate and severe earthquakes have struck different places in the world causing severe damage to reinforced concrete (RC) structures. Beam-column joints, being the key lateral and vertical load resisting members in RC structures are particularly vulnerable to failures in earthquakes and hence their retrofit is often the key to successful seismic retrofit strategy. Experimental investigations were taken up to study the behaviour of RC external beam- column joints retrofitted with CFRP and GFRP wraps. Also a new technique of providing additional reinforcement in the form of lacing was investigated for the beam-column joint to take care of the shear forces, which will be acting in the joint portion. The results of the experimental investigations goes to prove that in situations, where retrofi tting of structures is encountered, particularly when the stirrups are not provided as per design and in situations where the structure has to be retrofitted to meet recent seismic design provisions, it is possible to enhance the performance of the structural members of those structures by providing them with FRP wraps and RC jacketing with microconcrete. However, it is essential to use appropriate performance factors to evaluate the repair strategy adopted to arrive at meaningful conclusions.